NILAI-NILAI ISI PRASASTI KEDUKAN BUKIT SEBAGAI SUMBER BELAJAR SEJARAH DI SMA - Bardan.A, Kemas Muhammad; Sholeh, Kabib; Syafarudin, Nur (Universitas Batanghari Jambi, 2025)
The Kedukan Bukit Inscription considers values that can be used as a source of learning for high school. The purpose of this study was to determine the values of the contents of the Kedukan Bukit inscription as a source of learning history for high school. This research method uses qualitative descriptive. Data collection techniques in this study were through observation and library research. The results of this study indicate that in the contents of the Kedukan Bukit Inscription there are 11 values, namely religious values, technological values, maritime values, leadership values, struggle values, discipline values in valuing time, teamwork values, economic values, optimism values, responsibility values, and language values. The conclusion is that the values in the contents of the Kedukan Bukit Inscription can be used as a source of learning history in class X phase E, where the material is the Hindu-Buddhist kingdom. In fact, the values of the Kedukan Bukit Inscription can be associated with the P5 values contained in the Merdeka Curriculum.